Mechanisms of austenite growth during intercritical annealing in medium manganese steels. (1st January 2022) - Varanasi, Rama Srinivas; Lipińska-Chwałek, Marta; Mayer, Joachim; Gault, Baptiste; Ponge, Dirk
Abstract: The third-generation advanced high strength medium manganese (3–12 wt.%) steels typically consist of ultrafine-grained dual-phase (austenite-ferrite) microstructure, obtained through the intercritical annealing of martensite at temperatures typically ≤  0.5Tmelt, where the bulk diffusion of Mn is extremely slow. Yet, the manganese partitioning plays a prominent role in the austenite growth from the martensitic matrix during this annealing step. Therefore, the 'short circuit' diffusion paths provided by grain boundaries (GBs) and dislocations must be crucial to the austenite growth. However, this influence is not well understood across the literature. In the present work, we study the mechanisms of austenite growth in a cold-rolled intercritically annealed medium manganese steel of composition Fe-10Mn-0.05C–1.5Al (wt.%). We provide evidence of manganese transport to austenite through GB diffusion, GB migration and dislocation pipe diffusion. Furthermore, the influence of GB misorientation on austenite growth is also reported. Graphical abstract: Image, graphical abstract